Tooth whitening efficacy of pigmented rice gels containing carbamide peroxide - Adchareeya Kaewpinta (2018)
Carbamide peroxide (CP) is commonly used as a tooth whitening agent. However, efficacy of CP can be enhanced if it is in the suitable delivery system. In the present study, CP loaded in pigmented rice gels were developed and investigated for their physicochemical properties and tooth whitening efficacy. The modified pigmented rice of two varieties, Homnil (HN) and Doisket (DS) were prepared and used as a gelling agent. The outer appearance of the obtained rice gels containing 10% CP (CP-HN and CP-DS, respectively) were transparent and homogeneous texture. The pH of both rice gel bases was neutral but became slightly acidic after incorporating with CP. The adhesive property of HN gel was significantly higher than DS gels. In vitro drug release profile exhibited that the release of CP from CP-DS was significantly higher than CP-HN and the commercial gel (CP-CG), respectively. In vitro tooth whitening efficacy in 45 normal teeth revealed that the tooth whitening efficacy of the gels was time dependent. At the end of the treatment, CP-HN showed significantly higher tooth whitening efficacy than CP-DS and CP-CG, respectively. It is concluded that the physicochemical properties, particularly the adhesive and dissolution properties, play an important role in the tooth whitening efficacy of the CP gels.